First regional super ESPC a success on Kodiak Island, Alaska - Epstein, K. (National Renewable Energy Laboratory (U.S.), 2000)
The Coast Guard military base on Kodiak Island, Alaska, is the largest Coast Guard base in the world. By taking a leadership role in a pilot program to streamline Federal financing and procurement for energy saving projects, the Coast Guard is saving more than $220,000 a year in energy costs at this base. Using the Super ESPC (Energy Savings Performance Contracting) program, the Coast Guard was able to quickly contract with an experienced contractor with energy savings expertise. Working with ERI, one of FEMP's (Federal Energy Management Program) approved energy services contractors, the Coast Guard determined areas of potential energy savings and designed a retrofit to upgrade inefficient equipment and infrastructure. When energy-efficient modifications are complete, the base will be 30% more cost effective.